READING OPENING THROUGH MULTIPLE ARCHITECTURAL PERSPECTIVES: - Dhiracitta, Anindya; I Gusti Lanang Agung Nararya Pangjaya; Harry Kurniawan (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2024)
Most architectural designers develop an opening based only on its function and form. Other exciting things can be created further by exploring an opening. An opening is crucial as a design element to complement user activities and interactions. This paper examines ways to read openings from various architectural perspectives. Observations were carried out on objects in the form of several commercial buildings in Yogyakarta as a research method. The research results through the multi-perspective reading of the morphology of an opening show the influence of transparency, dimensions, shape, system, supporting components, opening height, and opening view framing in providing meaning and added value. The exploration that has been carried out then provides an understanding that the opening is not limited to its primary function as ventilation and lighting but can more broadly include the influence of its morphology on the perception it creates as a complete design presentation.